Volume 2: 28th Biennial Mechanisms and Robotics Conference, Parts a and B 2004
DOI: 10.1115/detc2004-57322
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Simulation of Cam Actuated Robotized Gearbox

Abstract: In this paper a simulation of the cam actuator of a robotized gearbox is presented. The actuator is a barrel cam which moves a pin according to a prescribed motion law. The model of contact, between cam and follower, is based on a finite elements approach of the theory of beam on continuous elastic foundation, modified by the authors to include the effect of shear on the deformation and dynamic effects. The foundation modulus is computed using Hertz theory taking also into account the change of principal curva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Furthermore, they observed that the wear does not affect the entire surface of the shaft, but mostly happened on specific spots. Pennestri et al [11] also based on the Reye's hypothesis, estimated the wear of a cam follower mechanism actuated robotized gearbox, in order to improve the design of the cam profile by achieving uniform wear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they observed that the wear does not affect the entire surface of the shaft, but mostly happened on specific spots. Pennestri et al [11] also based on the Reye's hypothesis, estimated the wear of a cam follower mechanism actuated robotized gearbox, in order to improve the design of the cam profile by achieving uniform wear.…”
Section: Introductionmentioning
confidence: 99%